Condensed Mitochondria Assemble Into the Acrosomal Matrix During Spermiogenesis - Ren, Mindong; Xu, Yang; Phoon, Colin K. L.; Erdjument-Bromage, Hediye; Neubert, Thomas A.; Rajan, Sujith; Hussain, M. Mahmood; Schlame, Michael (Frontiers in Cell and Developmental Biology, 2022)
Mammalian spermatogenesis is associated with the transient appearance of condensed mitochondria, a singularity of germ cells with unknown function. Using proteomic analysis, respirometry, and electron microscopy with tomography, we studied the development of condensed mitochondria. Condensed mitochondria arose from orthodox mitochondria during meiosis by progressive contraction of the matrix space, which was accompanied by an initial expansion and a subsequent reduction of the surface area of the inner membrane. Compared to orthodox mitochondria, condensed mitochondria respired more actively, had a higher concentration of respiratory enzymes and supercomplexes, and contained more proteins involved in protein import and expression. After the completion of meiosis, the abundance of condensed mitochondria declined, which coincided with the onset of the biogenesis of acrosomes. Immuno-electron microscopy and the analysis of sub-cellular fractions suggested that condensed mitochondria or their fragments were translocated into the lumen of the acrosome. Thus, condensed mitochondria are formed from orthodox mitochondria by extensive transformations in order to support the formation of the acrosomal matrix.